Analysis of Ambient Temperature Effect on Gas Turbine Centaur 40 at Sepinggan Production Field, Chevron Indonesia Company - adib, muhammad (JTM-ITI (Jurnal Teknik Mesin ITI), 2019)
Gas turbine Centaur 40 drive gas compressor operates 24 hours a day and continuously with monitored output parameters, namely pressure and the gas flow capacity In its operation, it is often found that the optimal output parameters are generated during low ambient temperatures, for example in the night, cloudy and rainy. This study is aimed to determine the effect of changes in ambient temperature on the gas turbine power. During operation and research was done, the independent variable used is ambient temperature at 24 – 33 0C at constant 100% rotation of the turbine shaft. The decrease in gas turbine performance is seen from the increase in Specific Fuel Consumption (SFC), a decrease in the power produced and thermal efficiency. Specific fuel consumption value from the calculation results is 0.06072 kg/kW.h at 24 0C ambient temperature and 0.06565 kg/kW.h at 33 0C ambient temperature. Power produced by the power turbine is 3532,657 HP at 24 0C ambient temperature and 3046,557 HP at 33 0C ambient temperature, while the thermal efficiency cycle is 54,159% at 24 0C ambient temperature and 49,727% at 33 0C ambient temperature. Keywords: gas turbine, ambient temperature, specific fuel consumption, thermal efficiency.